1998
DOI: 10.1021/om980908m
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Dichotomy in the Reactions of Cp2M(CH2CHMe) (M = Nb, Ta) with Catecholborane:  Generation of Boryl Complexes by Propylene Hydroboration and Propylene Loss

Abstract: A mixture of endo- and exo-Cp2TaH(CH2CHMe) (1a) and catecholborane (HBCat, Cat = 1,2-O2C6H4) reacted to give endo-Cp2TaH2(BCat) (2a) and n-PrBCat as the major products. Small quantities of exo-2a are also formed during the reaction. When the reaction was monitored by 1H NMR, the resonances for endo-1a were diminished relative to exo-1a, and eventually all of the olefin complex was consumed. The analogous reaction employing DBCat led to deuterium incorporation at the α-methylene position of n-PrBCat and the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Furthermore, a broad 1 H NMR singlet resonance (peak width at half height: 87.5 Hz) at d = À10.62 ppm suggested the presence of a hydride-like proton, and the 1 H{ 11 B} NMR spectra showed a sharper peak (width at half height: 17.5 Hz) for the same resonance, which is consistent with a Cr-H-B bridge existing in solution. [9] A COSY correlation between this signal and an olefinic proton served to reinforce the proposed connectivity of compound 3.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, a broad 1 H NMR singlet resonance (peak width at half height: 87.5 Hz) at d = À10.62 ppm suggested the presence of a hydride-like proton, and the 1 H{ 11 B} NMR spectra showed a sharper peak (width at half height: 17.5 Hz) for the same resonance, which is consistent with a Cr-H-B bridge existing in solution. [9] A COSY correlation between this signal and an olefinic proton served to reinforce the proposed connectivity of compound 3.…”
mentioning
confidence: 66%
“…As a result, the C=C bond is in position to share its electron density with the metal, and at the same time the boron-bound hydrogen H1 is aligned trans to the C1-O1 carbonyl group. The C5 À C6 bond length (1.3723 (17) + , which has a CÀC distance of 1.393 (9) . [11] The C5ÀB1 distance is in the expected range of CÀB single bonds (1.5482(18) ) but is surprisingly unperturbed by the close Cr-H-B association, the distance agreeing well with the vinylborane complex [(OC) 4 Fe{H 2 C = CHBCH 3 N(CH 3 ) 2 }] (4) of Schmid et al, in which the boron atom is distant from the metal center.…”
mentioning
confidence: 99%
“…Garcia and coworker have recently reported the r-borane complexes of nickel(0) [10]. Synthesis and bonding of the transition metal complexes containing residual BÁ Á ÁH interaction have been reported [11][12][13][14][15][16][17][18]. Mechanistic studies have revealed that r-borane complexes can be intermediates in catalytic hydroboration and borylation reactions [13,[19][20][21].…”
mentioning
confidence: 99%
“…153 This stepwise hydroboration^homologation approach has been shown to afford high enantioselectivity in the resulting products. 154 The synthesis, structures and reactivity of osmium boryl complexes of the type [Os(PPh 3 ) 2 (CO) n (C 8 H 4 Me-2)(Bcat)] (n 1,2) have been described and are claimed to be the ¢rst stable coordinatively unsaturated and saturated examples respectively of complexes containing simple boryl and s-bound ligands. Such complexes are interesting as they represent isolated intermediates in hydroboration reactions.…”
Section: Heterocycles Containing Boronmentioning
confidence: 99%